2009
DOI: 10.1134/s1063780x09100109
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the ignition of a methane-air mixture by a high-voltage nanosecond discharge

Abstract: International audienceThe ignition dynamics of a CH4: O2: N2: Ar = 1: 4: 15: 80 mixture by a high-voltage nanosecond discharge is simulated numerically with allowance for experimental data on the dynamics of the discharge current and discharge electric field. The calculated induction time agrees well with experimental data. It is shown that active particles produced in the discharge at a relatively low deposited energy can reduce the induction time by two orders of magnitude. Comparison of simulation results f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(51 citation statements)
references
References 36 publications
2
49
0
Order By: Relevance
“…To derive the rotational cross section of CH 4 , Müller et al 52 Theoretically, there are two classes of calculations: closecoupling method and variational calculation, see Itikawa and Mason 56 for details. Three papers [57][58][59] have been published based on close-coupling calculation for CH 4 . Among them, Abusalbi et al 57 reported the cross section only at one energy (10 eV).…”
Section: Rotational Excitation Cross Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…To derive the rotational cross section of CH 4 , Müller et al 52 Theoretically, there are two classes of calculations: closecoupling method and variational calculation, see Itikawa and Mason 56 for details. Three papers [57][58][59] have been published based on close-coupling calculation for CH 4 . Among them, Abusalbi et al 57 reported the cross section only at one energy (10 eV).…”
Section: Rotational Excitation Cross Sectionmentioning
confidence: 99%
“…Fits to the recommended total and partial ionization cross section using the formula of Janev and Reiter, 11 Eq. 4 , independent of the method applied, are to be considered as gross total ionization cross section, which is the total ion current collected, i.e., the charge-weighted sum of partial cross sections,…”
Section: Semi-empirical Estimates and Counting Ionization Cross Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the discharge energy is transferred into the excitation of internal degrees of freedom in the gas, a portion of the discharges energy is rapidly converted to the energy of translational degrees of freedom. The fraction of transmitted energy varies from 10% to 60% at different electric field [17]. The process of energy transfer and relaxation occurs in tens or hundreds of nanoseconds, which is less than the typical gas-dynamic time.…”
Section: Single-shot Successive Schlieren Images Of Npd In Airmentioning
confidence: 99%
“…While the discharges energy is transferred into the excitation of internal degrees of freedom in the gas (like the electronic excitation of N 2 molecules et al), a portion of the discharges energy is rapidly converted to the energy of translational degrees of freedom. The fraction of transmitted energy varies from 10 to 60 % at different electric field [21]. The process of energy transfer and relaxation occurs in a very short space of time, like the rotational-translational (RT) relaxation process requires only a few collisions.…”
Section: Single-shot Successive Schlieren Images Of Npd In Airmentioning
confidence: 99%